The campaign “This Is Public Health” in Italy, set up by a team of Public Health Schools in Northern Italy - Bucci, Daria; Rossi, Deanna; Croci, Roberto; Bellini, Lorenzo; Bonaldi, Filippo; Capraro, Michele; Frascella, Beatrice; Gaetti, Giovanni; Granata, Lucio; Solla, Daniele; Stirparo, Giuseppe; Bizzarro, Assunta; et al. (Acta Biomedica Atenei Parmensis, 2020)
Despite the great effort to raise awareness among health promotion, nowadays Public Health policies are not often recognized as important tools. For this reason, the Health in All Policies (HiAP) approach is instrumental in tackling this information gap. In 2018, the US Association of Schools and Programs of Public Health (ASPPH) launched an international campaign called “This is Public Health” (TIPH), whose aim was “to brand public health and raise awareness of how it affects individuals, communities and populations”. The Association of Schools of Public Health in the European Region (ASPHER), in coordination with ASPPH, decided to create a European campaign to support and to reproduce the American one, by opening a challenge among the European Public Health Schools. The Schools and Programs of PH of Vita-Salute “San Raffaele” University, Milan, University of Parma, University of Pavia and Politecnico of Milan won this bid. In this “briefing on” we present a report on the Italian project for raising awareness of Public Health among general population and health care personell.